Pitfalls in Ultrasound Diagnosis of Cesarean Scar Pregnancy - Ravi Selvaraj, Lakshmy (J Obstet Gynaecol India, 2017)
Cesarean scar pregnancy (CSP) is a rare kind of ectopic pregnancy implanted in the previous cesarean scar and has an increasing incidence over the past 30 years. As the suspicion is low, the diagnosis may be delayed or misinterpreted in ultrasound, leading to treatment strategies that might end up in uterine rupture or hysterectomy. The objective here is to review the ultrasound findings in CSP with varied presentations. Transabdominal and transvaginal sonography combined with color Doppler is a reliable tool for the diagnosis of CSP. When the gestational sac is seen in lower part of the uterine cavity, differentiation between threatened miscarriage, cervical pregnancy and CSP could be difficult. Not all cases of CSP present with typical ultrasound findings and a high index of suspicion is needed for diagnosis in these cases. An attempted curettage or MTP pill taken in an undiagnosed CSP often alters the typical findings. The possibility of CSP should also be considered in cases presenting with abnormal uterine bleeding and have a prior history of cesarean section. With lack of awareness about this condition, the diagnosis can often be missed either with MRI or in ultrasound. Correct interpretation and timely diagnosis save the mother from life-threatening complications and also preserves future fertility.